Hyperreality: Pemaknaan dalam Penggunaan Game Pokemon Go (Jurnal Kajian Media, 2017)
This study aims to determine hyperreality in gaming phenomenon Pokemon Go. To find out more about how to influence the use of augmented reality technology in a Pokemon game Go and also the standpoint of game players who shared Pokemon Go. This research approach uses qualitative research methods approach is the approach used to explain and describe the phenomenon - a phenomenon that occurs with the paradigm of phenomenology. Data collection techniques used were observation and in-depth interviews. Data were analysed using the method of transcendental Husserl's phenomenological approach that consists of objects (objects/phenomena), the deliberate, noema, noesis, intersubjective, intuition, and also meaning/essence of the object. Results from this study showed that hyperreality contained on the gaming phenomenon Pokemon Go is where players game Pokemon Go feel in your own world where there are a lot of monsters - monsters Pokemon as well as the arena - playing field as pokestop and also a gym and the players at will conduct their activities in their game world, where meanings, signs, code is no longer valid. Keywords: Pokemon Go, Hyperreality, Meaning